Indoor and outdoor air quality: a university cafeteria as a case study - Alves, Célia A. (2020)
A short but exhaustive air sampling campaign was conducted in a university cafeteria, an occupational environmental not yet studied. Carbonyls and volatile organic compounds were collected by passive diffusion samplers. Temperature, relative humidity, CO2, CO and particulate matter were continuously monitored indoors and outdoors. Simultaneous PM10 sampling with high and low volume instruments, equipped with quartz and Teflon filters, respectively, was performed during working hours and at night. The quartz filters were analysed for their carbonaceous content by a thermo-optical technique and organic constituents by GC-MS. Water-soluble ions and elements were analysed in the Teflon filters by ion chromatography and PIXE, respectively. Low air change rates (0.31–1.5 h−1) and infiltration factors of 0.14, for both PM2.5 and PM10, indicate poor ventilation conditions. Concentrations of both gaseous pollutants and particulate matter were much higher in the cafeteria than outdoors, showing strong variations throughout the day depending on occupancy and activities. The average concentration of indoor-generated PM10 was estimated to be 32 μg m−3. Organic compounds in PM10 included alkanes, PAHs, saccharides, phenolics, alcohols, acids, alkyl esters, triterpenoids, sterols, among others. The complex particle composition reveals the multiplicity of sources, formation reactions and removal processes, not yet fully known, and suggests the contribution from dust resuspension, abrasion and off-gassing of building materials, cooking emissions, tobacco smoke, and several consumer products. Many compounds are in the list of ingredients of personal care products, pesticides, plasticisers, flame retardants and psychoactive drugs. The inhalation cancer risks of metals and PAHs were found to be negligible.